PENGARUH KESADARAN, KUALITAS PELAYANAN DAN KONDISI KEUANAGAN TERHADAP KEMAUAN WAJIB PAJAK ORANG PRIBADI DENGAN KEPATUHAN PAJAK SEBAGAI VARIABEL INTERVENING (Studi Empiris pada KPP Pratama Rengat) - Mega Fatmawati Siagian; Vince Ratnawati; Sem Paulus Silalahi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of awareness , service quality andfinancial conditions on the willingness of taxpayers. This study also want toexamine whether compliance mediates the influence ofawareness , service quality and financial conditions on the willingnessof taxpayers. The population in this study a taxpayers which are registered inKPP Pratama Rengat with 180 respondents were selected using the accidentalsampling method. This study uses primary data by dissemination of thequestionnaires. Technical analysis for hypotheting that used in this study isStructural Equation Modeling (SEM-PLS), with Partial Least Square (PLS)6.0. The results showed that awareness, service quality and financialconditions affects the taxpayer premises unwillingness to levelssignificant <0.05. The study also found that compliance mediates the influence ofawareness , service quality and financial conditions on the willingnessof taxpayers with a significant level of <0.05.Keywords : Awareness , Quality Services, Financial Conditions , Compliance ,Willingness Obligatory Tax